A Correlational Study of Language Learning Strategies and Learner Autonomy among Graduate Students in English Education in Indonesia - Genti Putri Dwi Redjeki; Agus Widyantoro (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2024)
Various studies have highlighted the significance of language learning strategies in enhancing language competence. However, studies specifically examining the correlation between these strategies and learning autonomy are limited, particularly among graduate students in Indonesia. This study seeks to address this gap by examining the correlation between language learning strategies and learning autonomy among graduate students. Using quantitative methods, this study involved a correlation design on 136 graduate English language students at a state university in Indonesia. The instruments used were the Strategy Inventory for Language Learning (SILL) questionnaire developed by Oxford (1990) and the Learner Autonomy (LA) questionnaire developed by Chan and Spratt (2002). The analysis of the data involved descriptive statistics and Pearson product-moment correlation. The results revealed that the majority of graduate students utilized metacognitive strategies more frequently to acquire English skills, and they demonstrated a high level of autonomy. Furthermore, researchers discovered a positive correlation between language learning strategies and learner autonomy. The implications of this study indicate that the use of language learning strategies contributes to supporting learner autonomy. Therefore, it is important for educational institutions and lecturers to design curricula and learning activities that encourage the application of relevant strategies and the development of student autonomy. This not only helps students become more autonomous in the learning process but also improves the effectiveness of English language acquisition among graduate students.